2017
DOI: 10.1038/nrmicro.2016.176
|View full text |Cite
|
Sign up to set email alerts
|

Virus–host interactions and their roles in coral reef health and disease

Abstract: Coral reefs occur in nutrient-poor shallow waters, constitute biodiversity and productivity hotspots, and are threatened by anthropogenic disturbance. This Review provides an introduction to coral reef virology and emphasizes the links between viruses, coral mortality and reef ecosystem decline. We describe the distinctive benthic-associated and water-column- associated viromes that are unique to coral reefs, which have received less attention than viruses in open-ocean systems. We hypothesize that viruses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(168 citation statements)
references
References 156 publications
8
159
1
Order By: Relevance
“…Although we did not test the ecological and evolutionary consequences of variation in viral diversity in this study, it is probable that some members of the vampire bat viral community identified here have functional importance. For example, viral metagenomics has identified specific viral taxa associated with disease (Duerkop et al, 2018;Hannigan, Duhaime, Ruffin, Koumpouras, & Schloss, 2018;Ly et al, 2014;Norman et al, 2015) and the critical contributions of certain viral groups to overall ecosystem function (Emerson et al, 2018;Sunagawa et al, 2015;Thurber, Payet, Thurber, & Correa, 2017). Follow-up analyses could include targeting individual viral taxa that are linked with health or disease in other systems, examining associations between variation in viral diversity and host fitness, or testing interactions between viral communities and other components of the host microbiome.…”
Section: Viral Richnessmentioning
confidence: 99%
“…Although we did not test the ecological and evolutionary consequences of variation in viral diversity in this study, it is probable that some members of the vampire bat viral community identified here have functional importance. For example, viral metagenomics has identified specific viral taxa associated with disease (Duerkop et al, 2018;Hannigan, Duhaime, Ruffin, Koumpouras, & Schloss, 2018;Ly et al, 2014;Norman et al, 2015) and the critical contributions of certain viral groups to overall ecosystem function (Emerson et al, 2018;Sunagawa et al, 2015;Thurber, Payet, Thurber, & Correa, 2017). Follow-up analyses could include targeting individual viral taxa that are linked with health or disease in other systems, examining associations between variation in viral diversity and host fitness, or testing interactions between viral communities and other components of the host microbiome.…”
Section: Viral Richnessmentioning
confidence: 99%
“…One area in particular that has been largely overlooked until recently is the role that coral‐ and Symbiodinium ‐associated viruses may play in coral disease or dysfunction of the symbiosis. Several studies have provided evidence that viruses infect corals and Symbiodinium cells (reviewed in Vega Thurber et al ., ). Whether viruses are the causative agents of any coral diseases has not yet been proven conclusively.…”
Section: Introductionmentioning
confidence: 97%
“…Third, phages may be agents of lateral gene transfer between microbial members of the holobiont 95 . Also, phage-induced and virus-induced mortality of bacterial and host cells may contribute to nutrient remineralization within the system, altering holobiont physiology and microbial ecology (the 'revolving door' hypothesis) 96 . Another mechanism by which viruses could influence coral-associated bacterial communities is through genetic rearrangement.…”
Section: Potential Involvement Of Microbes In Coral Acclimatizationmentioning
confidence: 99%